Collaboration, communication, support, and relationships in the context of e-commerce within the franchising sector. (17th February 2022) - Kremez, Zhanna; Frazer, Lorelle; Quach, Sara; Thaichon, Park
ABSTRACT: This research aims to investigate how ecommerce influences elements of the franchising sector that have adopted an ecommerce strategy. A multiple case-study approach was selected to gain a comprehensive understanding of franchise organisations following implementation in their traditional service or retail businesses. The findings covered, but were not limited to, (a) franchise relationships, (b) franchisor leadership, (c) communication at the franchise network level, (d) collaboration with franchisees, and (e) training and support. The paper offers meaningful outcomes including (a) a framework for franchisee communication and participation, and (b) a model for franchisee acceptance and readiness for change, as well as effective communication in the franchise network. Finally, from the interviews conducted with franchise practitioners, certain practical recommendations have been made that will serve the franchise sector.